Can we address cancer disparities in immigrants by improving cancer literacy through English as a second language instruction?. Issue 2 (27th March 2018) - Hughes, Donna L; Flight, Ingrid; Chapman, Janine; Wilson, Carlene
Abstract : Non-English speaking immigrants can have poor cancer literacy. This may be improved through training via English as a Second Language Instruction. The paper describes this approach and an evaluation framework. Abstract: In many Western countries, immigrants exhibit disparities in cancer incidence and mortality, and variable uptake of cancer prevention services. New immigrants may not be aware of cancer risks pertinent to their new country, or prevention resources. Traditional cancer prevention health messaging may not be accessible for cultural, language, or literacy reasons. New methods are needed. In North America, health message delivery via English classes for immigrants is showing potential as an efficacious and a feasible way to reach immigrants at the same time improving language skills. Interventions published to date are promising but limited in their ability to generalize or be adapted to a variety of populations and settings. This concept paper aims to synthesize previous findings and identify ways to improve and advance the translation potential of this approach. We propose that this could be achieved by (i) using a translation framework to guide intervention planning, development, implementation, and evaluation; (ii) encouraging and evaluating health message spread throughout language learners' social networks; and (iii) incorporating cultural sensitivity into the curriculum. A pilot project following these recommendations is planned for Australia and will be discussed. These recommendations could serve as a framework to fit the requirements of immigrant language programs in other countries and other health topics.